Associations Between Anticholinergic Burden and Adverse Health Outcomes in Parkinson Disease - Data - Crispo, James A. G.; Willis, Allison W.; Thibault, Dylan P.; Fortin, Yannick; Hays, Harlen D.; McNair, Douglas S.; Bjerre, Lise M.; Kohen, Dafna E.; Perez-Lloret, Santiago; Mattison, Donald R.; Krewski, Daniel (Université d'Ottawa | University of Ottawa, 2016)
Background: Elderly adults should avoid medications with anticholinergic effects since they may increase the risk of adverse events, including falls, delirium, and cognitive impairment. However, data on anticholinergic burden are limited in subpopulations, such as individuals with Parkinson disease (PD). The objective of this study was to determine whether anticholinergic burden was associated with adverse outcomes in a PD inpatient population. Methods: Using the Cerner Health Facts® database, we retrospectively examined anticholinergic medication use, diagnoses, and hospital revisits within a cohort of 16,302 PD inpatients admitted to a Cerner hospital between 2000 and 2011. Anticholinergic burden was computed using the Anticholinergic Risk Scale (ARS). Primary outcomes were associations between ARS score and diagnosis of fracture and delirium. Secondary outcomes included associations between ARS score and 30-day hospital revisits. Results: Many individuals (57.8%) were prescribed non-PD medications with moderate to very strong anticholinergic potential. Individuals with the greatest ARS score (≥4) were more likely to be diagnosed with fractures (adjusted odds ratio (AOR): 1.56, 95% CI: 1.29-1.88) and delirium (AOR: 1.61, 95% CI: 1.08-2.40) relative to those with no anticholinergic burden. Similarly, inpatients with the greatest ARS score were more likely to visit the emergency department (adjusted hazard ratio (AHR): 1.32, 95% CI: 1.10-1.58) and be readmitted (AHR: 1.16, 95% CI: 1.01-1.33) within 30-days of discharge. Conclusions: We found a positive association between increased anticholinergic burden and adverse outcomes among individuals with PD. Additional pharmacovigilance studies are needed to better understand risks associated with anticholinergic medication use in PD.